Therapeutic potential of genetically modified adult stem cells for osteopenia - Kumar, Sanjay (2009)
Adult stem cells have therapeutic potential because of their intrinsic capacity for self-renewal, especially for bone regeneration. The present study demonstrates the utility of ex vivo modified mesenchymal stem cells (MSC) to enhance bone density in an immunocompetent mouse model of osteopenia. MSC were transduced ex vivo with a recombinant adeno-associated virus 2 (rAAV) expressing BMP-2 under the transcriptional control of collagen type-1α promoter. To enrich bone homing in vivo, the cells were further modified to transiently express the mouse α-4 integrin. The modified MSC were systemically administered to ovariectomized, female C57BL/6 mice. Effects of the therapy were determined by dual energy x-ray absorptiometry, 3D micro-CT, histology, and immunohistochemistry for up to six months. Results indicated that mice transplanted with MSC expressing BMP-2 showed significant increase in bone mineral density and bone mineral content(p<0.001) with relatively better proliferative capabilities of bone marrow stromal cells and higher osteocompetent pool of cells compared to control animals. Micro-CT analysis of femora and other bone histomorphometric analyses indicated more trabecular bone following MSC-BMP-2 therapy. Results obtained by transplanting genetically modified MSC from GFP transgenic mouse suggested that production of BMP2 from transplanted MSC also influenced the mobilization of endogenous progenitors for new bone formation.